Walking the Talk? What Employers Say Versus What They Do - Pager, Devah; Quillian, Lincoln (American Sociological Review, 2005)
This article considers the relationship between employers' attitudes toward hiring exoffenders and their actual hiring behavior. Using data from an experimental audit study of entry-level jobs matched with a telephone survey of the same employers, the authors compare employers' willingness to hire black and white ex-offenders, as represented both by their self-reports and by their decisions in actual hiring situations. Employers who indicated a greater likelihood of hiring ex-offenders in the survey were no more likely to hire an ex-offender in practice. Furthermore, although the survey results indicated no difference in the likelihood of hiring black versus white ex-offenders, audit results show large differences by race. These comparisons suggest that employer surveys-even those using an experimental design to control for social desirability bias-may be insufficient for drawing conclusions about the actual level of hiring discrimination against stigmatized groups.